Caring about Carework : Lifting Constraints to the Productivity of Women Farmers in the Democratic Republic of the Congo - Donald, Aletheia; Vaillant, Julia; Campos, Francisco; Cucagna, Maria Emilia (World Bank, Washington, DC, 2018)
Women farmers in the Western Democratic Republic of Congo (DRC) bear the disproportionate burden of unpaid care work. Women spend less time than men on their plots and more time on domestic work. The authors use a combination of consultations in the field, desk research, and primary data collection to understand the patterns of time allocation in rural households in Western DRC. The gender differences in time allocation are striking where the female plot managers do 1 hour and 52 minutes more of domestic work per day than male plot managers. The gender differences are higher in male-headed households, and female plot managers spend significantly more time taking care of children when farming or going to market than their male counterparts. The agricultural productivity of female plot managers is on average twenty six percent lower than that of male plot managers. Having young children is associated with lower productivity for women but not for men. With the support of various stakeholders, the authors will pilot the provision of childcare services in the targeted region. The authors will rigorously evaluate the importance of these services on women’s time allocation to productive activities, as well as their productivity.